Counseling Using Animated Video on the Level of Knowledge among Students at State Elementary School 11 of Manado - I Ketut Harapan; Youla Karamoy; Mustapa Bidjuni (Poltekkes Kemenkes Kupang, 2023)
Dental and oral health problems may exist due to several factors, including behavioral factors. Behavioral factors can be managed through certain interventions. Promotive efforts such as counseling can increase knowledge on dental and oral health. This study aims to determine the effect of counseling using animated video on the level of knowledge on how to brush teeth among students at State Elementary School 11 of Manado. This was an analytical study with a One Group Pretest-Posttest design conducted in June 2022 at State Elementary School 11 of Manado. The total population involved 30 people, and the samples were selected using total sampling technique. Data were analyzed using paired sample t-test. Data collection instrument used a questionnaire to assess the level of knowledge on how to brush teeth. The results showed that the mean pre-test level of knowledge on how to brush teeth was 22.9333 with a standard deviation of 1.87. Based on the results of the paired sample t-test, the mean difference in the level of knowledge on brushing teeth between the pre and post-tests was -5.833 with a standard deviation of 2.320. In addition, it was obtained a t count value of -13.768 > t table of 1.699 at df 29, with a p-value of <0.05. It can be concluded that there was a difference in the level of knowledge between before and after counseling using animated video among students at State Elementary School 11 of Manado. Further study is recommended to use other alternative media to increase students' knowledge.